Transforming the Cement Industry into a Key Environmental Infrastructure for Urban Ecosystem: A Case Study of an Industrial City in China. (28th July 2017) - Cao, Xin; Wen, Zongguo; Tian, Haikui; De Clercq, Djavan; Qu, Lili
Summary: Under the dual pressure of environmental constraints and increasingly thin profit margins, the cement industry in China is in a predicament. To alleviate the environmental and the economic pressure of the cement industry and to tackle the problem of delayed environmental infrastructure construction, this article introduced an urban ecosystem in which the cement industry was transformed into an effective complement to environmental infrastructure. The Xinfeng Cement Industrial Park in China, which has a production capacity of 5 million tonnes per annum (Mt/a) of clinker, was chosen as a case study. Our methodology involved proposing technologies to develop an efficient cement plant‐centered urban ecosystem; evaluating its environmental and economic performance; identifying barriers in its promotion; and proposing supportive policies. Results showed that the city's waste recycling ratio rose from about 50% to 70%, saving 0.6 Mt/a of coal equivalent and reducing about 3.0 Mt/a of resulting carbon dioxide (CO2 ) emissions. The life span of the city's landfill site was extended by about 30 years. The total investment was 3.2 billion yuan (about US480 million), 1 with an average payback period of 3 years. The Xinfeng Cement Industrial Park was transformed from an energy‐intensive consumer and a significant CO2 emitter to a key industrial waste recycler, a crucial municipal waste co‐processor, an important new building material supplier, and a potential energy producer. Last, the "not‐in‐my‐back‐yard" (NIMBY) effect from constructing new environmental infrastructure was also avoided.